1992
DOI: 10.1038/sc.1992.112
|View full text |Cite
|
Sign up to set email alerts
|

Motor vehicle crashes and spinal injury

Abstract: Accident reports for 67 patients admitted to 3 spinal cord injury units III Australia in 1987 as a result of motor vehicle accidents were examined. Two thirds of the accidents occurred during the Friday-Saturday-Sunday leisure period and about 60% occurred during the November-February Australian summer holiday season. This conforms to the general Australian pattern of road trauma which is predominantly a consequence of leisure travel. The likelihood of a road traffic injury resulting in damage to the spinal co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
8
0
1

Year Published

1995
1995
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 4 publications
2
8
0
1
Order By: Relevance
“…The high male:female ratio found in the present study was also described in previous studies on SCI 2,3,14,18 as well as in the Israeli Trauma Registration of people injured in road accidents. The gender ratio was higher in SCI than in other road accident victims, probably because of the higher proportion of car and motorcycle riders (who are mainly men) in the first group.…”
Section: Gendersupporting
confidence: 69%
See 3 more Smart Citations
“…The high male:female ratio found in the present study was also described in previous studies on SCI 2,3,14,18 as well as in the Israeli Trauma Registration of people injured in road accidents. The gender ratio was higher in SCI than in other road accident victims, probably because of the higher proportion of car and motorcycle riders (who are mainly men) in the first group.…”
Section: Gendersupporting
confidence: 69%
“…In Thailand and Australia, they cause about 50% of SCIs. 14,15 An Australian study showed an increase in SCI following road accidents, probably because of the increased rate of seat belts usage, which prevented death but not SCI.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…27 Several authors previously investigated factors that predispose to SCI after an MVC. 3,28,40,44,47 These previous studies were generally based on subsets of data from a single institution or state and frequently included injuries sustained not just by vehicle occupants but also by pedestrians and motorcycle riders involved in the collision, who are subject to different mechanisms of injury. 3,29,44 Some authors reported an increased risk of SCI after rollover collisions compared with that after collisions without vehicle rollover, after single-vehicle collisions compared with that after multiple-vehicle collisions, and in occupants of sports utility vehicles compared with those in sedans.…”
mentioning
confidence: 99%